(untitled) (Acta Scientiarum. Agronomy, 2017)
The peach tree (Prunus persica) is a fruit species native to temperate climates that requires a chill during its hibernal period to overcome dormancy. However, due to genetic breeding, varieties are currently grown in subtropical and tropical regions where there are low occurrences of chill during this phenological stage. This study evaluated the adaptability and stability of the reproductive and vegetative phases of peach tree cultivars in a subtropical climate. An experiment was designed in randomized blocks with split time plots, with 23 peach tree cultivars and four replications, with each replication consisting of one plant and four shoots. The years of evaluated (plots) and the cultivars (subplots) were considered to be treatments. The relative rates of budburst (RRB), flowering (RRF), shoot formation (SF) and fruit set (FS), average time of budburst (ATB) and flowering (ATF), duration of budburst (DB) and flowering (DF) and number of hours with temperatures below 7.20°C were evaluated during the experimental period. The cultivars ‘Bonão’, ‘Ouromel-4’, ‘Libra’ and ‘Maciel’ demonstrated greater adaptability during the vegetative phase, whereas‘Ouromel-4’ and ‘Libra’ demonstrated greater adaptability and stability during the reproductive phase of peach trees in a subtropical climate.